Bank Power and Cash Holdings: Evidence from Japan - Pinkowitz, Lee; Williamson, Rohan (Review of Financial Studies, 2001)
Using industrial firms from the United States, Germany, and Japan, we examine the effect of bank power on cash holdings. We show that Japanese firms hold more cash than U.S. or German firms. We also document that Japanese cash balances are affected by the monopoly power of banks. During periods with powerful banks, firms’ high cash holdings are consistent with banks extracting rents. When banks weakened, Japanese cash levels became more like U.S. firms. We conclude that strong Japanese banks persuade firms to hold large cash balances. This is contrary to widely held beliefs about the Japanese governance system.